Flouroscopic versus conventional epidural blood patch in obstetrics: A retrospective cohort study. Issue 5 (4th March 2022) - Orbach‐Zinger, Sharon; Lekar Leibzon, Margarita; Gonen, Ophir; Zribi, Benjamin; Wazwaz, Susan A.; Binyamin, Yair; Heesen, Michael; Matatov, Yuri; Shimon, Orit; Eidelman, Leonid A.
Abstract: Background: Epidural blood patch is a common effective treatment for postdural puncture headache after accidental dural puncture during labor and may be done in conventional or fluoroscopy‐guided methods. The aim of this study was to compare intensity of headache at the time of discharge from the hospital and to compare blood volumes injected in conventional epidural blood patches versus fluoroscopic‐guided blood patches and evaluate the side effects of both method of treatment. Methods: Between the years 2010 and 2020, 84 patients who were diagnosed with postdural puncture headache received either a conventional epidural blood patch or a fluoroscopic‐guided blood patch. Blood volumes were compared and evaluation of side effects was made based on data collected during and after the procedure. Results: Eighty‐four patients were included in this study. Fifty‐two women in the conventional epidural blood patch group and 32 in the fluoroscopic‐guided blood patch group. Women in the conventional epidural blood patch group received statistically significantly higher doses of blood than women in the fluoroscopic‐guided blood patch group: conventional method 29 ml IQR [23‐36] versus fluoroscopic method 16 ml, IQR [12‐18], p  < .001 with no difference in headache pain intensity at hospital release. There was no difference between groups in hospital length of stay, or persistent PDPH. There was also no difference chronic headache or backache between the two groups. Conclusions: Women who received fluoroscopic epidural blood patch required a much lower volume of blood injected while there was no difference between groups in headache pain intensity at discharge.